The Legal Fundamentals for the Sustainable Development of the Industrial Enterprises while the Introduction of the Innovative Functional Units - Arsentieva, Olena; Klius, Yuliia (European Journal of Sustainable Development, 2020)
In modern conditions, innovative activity is a special purposeful systematic set of measures to use innovative potential in order to achieve a new quality in the economic system in the process of ensuring its sustainable development. The implementation of innovative projects by industrial enterprises leads to disturbing influences in the form of innovative structural changes in the implementation of innovative structural units, affects the stability of economic systems and the effectiveness of their innovative activities. The presence of the legal grounds for changing the organizational structure of the enterprise in connection with the implementation of the activities aimed at the development of innovative goods and products is a prerequisite for the introduction of innovative units at an industrial enterprise. It should be noted that the regulatory framework governing innovative activity is quite contradictory and imperfect due to the lack of certain consistency regarding the definition of basic concepts and the existing conflict and inconsistency of legal regulation of relations in the field of innovative activity, so the relevance of its research and analysis is beyond doubt. Keywords: legal fundamentals, innovative unit, industrial enterprises, sustainable development